Penerapan Statistical Quality Control Pada Masa Inkubasi Pengalengan Ikan Lemuru di CV. Pasific Harvest Banyuwangi - Elly Kurniawati; Exshi Nabilla Nabilla; Resti Pranata Putri (JOFE : Journal of Food Engineering, 2023)
Fish canning is a form of modern fish processing and preservation which is hermetically packed and then sterilized. Hermetic packaging means that the closure is very tight, so it cannot be penetrated by air, water, oxidation damage or changes in taste. This research was conducted to determine the quality control of canned lemuru products, especially during the incubation process at CV. Pacific Harvest Banyuwangi. The research method used is interview, observation, and literature study. The necessary data include production data, data on the number of defects in the incubation process, and types of defects in the incubation process. Method Statistical Quality Control (SQC) is used in controlling quality from the initial process to the finished product, as well as controlling the production process with certain quality standards that have been agreed upon by the company. Statistical quality control is a problem-solving technique used to monitor, control, analyze, manage, and improve products and processes using statistical methods. In this study, data analysis was done by making a check sheet (Check Sheet), Pareto Diagram,Scatter Diagrams, and Fishbone Diagram. In processing the data that has been obtained will use the application Microsoft Excel and Minitab 16 as research data processing. In the final results of the research, recommendations for appropriate improvements will be made for quality control of the quality of canned lemuru products so that they can be consumed and distributed.